Determinants and Consequences of Blockchain Technology Adoption in the Chinese Listed Firms - He, Chengliu (Curtin University, 2024)
This thesis comprises three essays, which are dedicated to exploring the determinants and consequences of blockchain technology (BT) adoption by listed companies in China. The first essay examines the factors that affect the implementation of BT in firms from the perspective of internal corporate governance and external environment. Firms’ litigation risks and audit pricing are considered the main economic consequences of the adoption of BT in the second and third essays respectively.